HOTS-Based Worksheet in English Learning Activity for Eight Grade Students of Junior High School - Kenny Tirtayasa, I Komang; Nitiasih, Putu Kerti; Budiarta, Luh Gd Rahayu (Universitas Pendidikan Ganesha, 2022)
Teachers should be able to develop learning activities that offer meaningful learning to students and improve students' English skills. Higher Order Thinking Skills, or HOTS, are the current solution to support the development of student's abilities. This study has the purpose to develop a students' worksheet in a form of a supplementary book by promoting HOTS for eighth-grade students to implement curriculum 2013. The book is for the eighth grade in the second semester of junior high school students. This research implements D&D (Design and Development research) methods with four steps which are Analysis, Design, Development, and Evaluation. The researcher employed random sampling and participants in this study were eighth-grade Junior High School students. In collecting the data, the researcher conducted learning process observation, teacher interview, document analysis, and expert judgment. The result of the study found that the HOTS-Based Worksheet can use as a guide for leading and educating students when reading books. The use of this book makes learning more fun, interesting, and visually appealing for students. This worksheet can also help students improve their English language skills and critical thinking skills. The expert evaluation findings show that this product falls into the category of